Acoustic pharyngometry vs lateral cephalometry: A comparative evaluation of pharyngeal airway dimensions in patients with skeletal class I and skeletal class II malocclusion. Issue 3 (September 2019) - Kumar, Sunil; Jayan, B.; Kumar, M.P. Prassana; Sharma, Mohit; Nehra, Karan; Bansal, Amit Kumar
Abstract: Purpose: The objective of this study was to study the difference in upper airway parameters using two different techniques, i.e. with lateral cephalometry vis-a-vis acoustic pharyngometry in skeletal class I and class II subjects and to find any correlation in airway parameters recorded on cephalogram and acoustic pharyngometer. Materials and methods: Sixty orthodontic patients with average growth pattern (FMA = 22–28°) were divided in to two groups based on sagittal jaw relationship. Pharyngeal airway dimensions were measured by two different techniques, i.e. on lateral cephalogram and acoustic Pharyngometry. The airway dimensions were compared across both the groups using these techniques. Results: The linear airway parameters and total oropharyngeal area measured on lateral cephalogram ( P -value 0.008) were significantly higher in skeletal class I patients. Total oropharyngeal area measured using acoustic pharyngometry was significantly higher in skeletal class I patients ( P  = 0.009). The average area on lateral cephalogram and on acoustic pharyngometry did not differ significantly in skeletal class I group ( P  = 0.590). The comparison of average area in skeletal class II malocclusion group on lateral cephalogram and acoustic pharyngometry also did not differ significantly ( P  = 0.603). The average area on lateral cephalogram obtained by digital planimeter and acoustic pharyngometry did not differ significantly in both the classes of malocclusion ( P  = 0.405). Conclusion: The null hypothesis is rejected as there is significant difference in airway dimensions in skeletal class I and class II subjects and there is a positive correlation in airway parameters as recorded on lateral cephalogram and acoustic pharyngometer.